Cell-Free Therapeutic Mechanisms of AD-MSC Secretome in Type 2 Diabetes Mellitus: Literature Review - Padilla, Putri Rahma; Marlina, Marlina; Tjong, Djong Hon (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder with a globally increasing prevalence, while conventional therapies often fail to halt disease progression. The secretome derived from adipose-derived mesenchymal stem cells (AD-MSCs) holds great potential as a cell-free therapy strategy, as it contains various bioactive molecules, cytokines, and extracellular vesicles that regulate glucose metabolism and modulate immune responses. This review discusses the molecular components of AD-MSC secretome, its mechanisms in enhancing insulin sensitivity and protecting pancreatic β-cells, as well as the challenges in its clinical application. Based on literature from 2018–2025 in PubMed, Scopus, and Web of Science, AD-MSC secretome has been shown to enhance IRS-1 phosphorylation, activate the PI3K/Akt pathway, and promote GLUT4 translocation while suppressing chronic inflammation. Growth factors (HGF, IGF-1, VEGF) and microRNAs (miR-126, miR-21, miR-146a) contribute to β-cell regeneration. Donor variability, culture conditions, and isolation methods affect secretome quality, which can be optimized through preconditioning or genetic modification.